Method for producing catalyst for olefin polymerization
Patent Information
- Application Number
- JP2022527530
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-27
- Filing Date
- 2021-03-15
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-03-15
AI Technical Summary
【0015】 本発明によれば、固体触媒成分(A)および有機アルミニウム化合物(B)から選ばれる少なくとも一方が、一つ以上のビニル基を有する炭化水素化合物と予め接触処理されたものであることにより、固体触媒成分の表面にポリオレフィンの保護膜が形成され易くなる。その結果、有機アルミニウム化合物による固体触媒成分中のチタン活性点への過剰な活性化反応を抑制し、オレフィン類重合用触媒の失活を抑制しつつ安定した状態で重合反応に供し得ると考えられる。
Smart Images

Figure 0007644758000001 
Figure 0007644758000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a catalyst for olefin polymerization, a catalyst for olefin polymerization, and a method for producing an olefin polymer. [Background technology]
[0002] Conventionally, catalysts obtained by mutually contacting a solid catalyst component containing a transition metal catalyst component such as titanium with a typical metal catalyst component such as aluminum have been widely known as catalysts for polymerizing olefins (see, for example, Patent Document 1).
[0003] The emergence of supported catalysts using magnesium compounds as supports has dramatically increased the polymerization activity of olefin polymerization catalysts. Furthermore, the addition of electron donors such as ester compounds makes it possible to produce polymers with high stereoregularity from α-olefins with three or more carbon atoms.
[0004] For example, Patent Document 2 proposes a method for polymerizing propylene using a solid titanium catalyst component carrying an electron donor compound such as a phthalate ester, and an organoaluminum compound and an organosilicon compound having at least one Si-O-C bond as co-catalyst components. Many documents, including the above patent document, propose methods for producing highly stereoregular polymers in high yields using a phthalate ester as an electron donor compound.
[0005] However, di-n-butyl phthalate and benzyl butyl phthalate, which are types of phthalate esters, have been identified as Substances of Very High Concern (SVHC) under the European Registration, Evaluation, Authorization and Restriction of Chemicals (REACH) regulation, and there is an increasing demand to switch to catalyst systems that do not use SVHC substances in order to reduce the environmental impact.
[0006] Known solid catalyst components using succinic acid esters, maleic acid esters, malonic acid esters, diethers, etc. are electron donor compounds that are not subject to SVHC regulations. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2015 / 012963 [Patent Document 2] Japanese Patent Application Publication No. 57-63310 Summary of the Invention [Problem to be solved by the invention]
[0008] However, it is known that a solid catalyst component using a compound not subject to SVHC regulation as an electron donor compound is difficult to exhibit the same performance as a solid catalyst component using a phthalate ester. In particular, in a polymerization facility in which a process is performed in which a solid catalyst component, an organoaluminum compound, and, if necessary, an external electron donor compound are contacted under an inert gas atmosphere such as a nitrogen atmosphere, the activity of a solid catalyst component using an electron donor compound not subject to SVHC regulation tends to decrease significantly. Under these circumstances, further improvement has been required for solid catalyst components using electron donor compounds not subject to SVHC regulation.
[0009] The present inventors have considered this point and found that in the above process, when the solid catalyst component, the organoaluminum compound, and optionally the external electron donor compound are brought into contact with each other, an excessive reaction proceeds. In this case, there are concerns that the internal electron donor compound may be desorbed from the solid catalyst component, an exchange reaction may occur between the internal electron donor compound and the organosilicon compound, or the solid catalyst component may be excessively activated by the organoaluminum compound.
[0010] For this reason, even if olefins are polymerized using a polymerization catalyst under an inert gas atmosphere such as a nitrogen atmosphere, it is considered that polyolefins are not formed on the surface of the polymerization catalyst, and deactivation of catalytic active sites proceeds due to excessive reaction. In particular, it has been found that when a so-called non-phthalate type internal electron donor compound not having a phthalate ester structure is used instead of an internal electron donor compound having an aromatic ring structure directly bonded to a carboxylate ester residue, i.e., a phthalate ester structure, is used, the compound is strongly susceptible to the influence of organoaluminum.
[0011] It has also been found that as the deactivation of the catalytic active sites proceeds, the catalytic activity and stereoregularity of the olefin polymerization catalyst tend to decrease.
[0012] Under these circumstances, an object of the present invention is to provide a method for producing a catalyst for olefin polymerization, which exhibits excellent catalytic activity during olefin polymerization by suppressing a decrease in polymerization activity due to early deactivation of active sites after catalyst formation, and is capable of producing olefin polymers with excellent stereoregularity, as well as a method for producing the catalyst for olefin polymerization and an olefin polymer. [Means for solving the problem]
[0013] Means for Solving the Technical Problems The present inventors have conducted intensive research in order to solve the above-mentioned technical problems, and have found that the above-mentioned technical problems can be solved by a method for producing an olefin polymerization catalyst by mutually contacting a solid catalyst component (A) containing magnesium, titanium, a halogen, and an internal electron donor compound with an organoaluminum compound (B), in which at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) has been previously contacted with a hydrocarbon compound having one or more vinyl groups, and have completed the present invention based on this finding.
[0014] That is, the present invention provides (1) a solid catalyst component (A) containing magnesium, titanium, a halogen, and an internal electron donor compound; The following general formula (I): R1 p AlQ 3-p (I) (wherein R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is a real number such that 0 < p ≦ 3.) A method for producing a catalyst for olefin polymerization by bringing into contact with each other an organoaluminum compound (B) represented by at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) is previously contact-treated with a hydrocarbon compound having one or more vinyl groups A method for producing a catalyst for olefin polymerization, characterized in that (2) The method for producing a catalyst for olefin polymerization according to (1) above, wherein the solid catalyst component (A) is previously contact-treated with a hydrocarbon compound having one or more vinyl groups (3) The method for producing a catalyst for olefin polymerization according to (1) above, wherein the organoaluminum compound (B) is previously contact-treated with a hydrocarbon compound having one or more vinyl groups (4) The amount of at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) that is previously contact-treated with a hydrocarbon compound having one or more vinyl groups is 1 mole or more per mole of titanium constituting the solid catalyst component (A) used for the production of the catalyst for olefin polymerization. A method for producing a catalyst for olefin polymerization according to (1) above, characterized in that (5) The method for producing a catalyst for olefin polymerization according to (1) above, wherein the hydrocarbon compound having one or more vinyl groups is one or more selected from ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1,4-hexadiene, 1,5-hexadiene, 1,6-octadiene, 1,7-octadiene, 1-heptene, 1-octene, vinylcyclohexane and vinylcyclohexene (6) A solid catalyst component (A) containing magnesium, titanium, a halogen and an internal electron donor compound, and The following general formula (I); R 1 p AlQ 3-p (I) (In the formula, R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is a real number satisfying 0 < p ≤ 3.) and an organoaluminum compound (B) represented by a hydrocarbon compound having one or more vinyl groups, and the hydrocarbon compound having one or more vinyl groups is contained in an amount of at least 0.1% by mass based on the total weight of titanium contained in the solid catalyst component (A). A catalyst for olefin polymerization, characterized in that (7) The hydrocarbon compound having one or more vinyl groups is at least one selected from ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1,4-hexadiene, 1,5-hexadiene, 1,6-octadiene, 1,7-octadiene, 1-heptene, 1-octene, vinylcyclohexane, and vinylcyclohexene The catalyst for olefin polymerization according to (6) above, characterized in that (8) A method for producing an olefin polymer, characterized by polymerizing olefins using the catalyst for olefin polymerization obtained by the production method according to any one of (1) to (5) above or the catalyst for olefin polymerization according to (6) or (7) above is provided.
Advantages of the Invention
[0015] According to the present invention, at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) is previously contact-treated with a hydrocarbon compound having one or more vinyl groups, whereby a protective film of polyolefin is likely to be formed on the surface of the solid catalyst component. As a result, it is considered that an excessive activation reaction of the titanium active sites in the solid catalyst component by the organoaluminum compound can be suppressed, and the catalyst for olefin polymerization can be subjected to the polymerization reaction in a stable state while suppressing the deactivation of the catalyst.
[0016] Therefore, according to the present invention, after the catalyst is formed, a method for producing a catalyst for olefin polymerization that can suppress a decrease in polymerization activity due to early deactivation of active sites, exhibit excellent catalyst activity during the polymerization of olefins, and produce an olefin polymer excellent in stereoregularity, a catalyst for olefin polymerization, and a method for producing an olefin polymer can be provided.
Embodiments for Carrying Out the Invention
[0017] <Method for Producing Catalyst for Olefin Polymerization> The method for producing a catalyst for olefin polymerization according to the present invention comprises a solid catalyst component (A) containing magnesium, titanium, a halogen, and an internal electron-donating compound, and the following general formula (I); R 1 p AlQ 3-p (I) (In the formula, R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is a real number satisfying 0 < p ≤ 3.) A method for producing a catalyst for olefin polymerization by bringing into contact with each other an organoaluminum compound (B) represented by wherein at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) is previously contact-treated with a hydrocarbon compound having one or more vinyl groups and is characterized by this.
[0018] In the method for producing an olefin polymerization catalyst according to the present invention, the solid catalyst component (A) is suitably one which contains an internal electron donor compound which contains magnesium, titanium and a halogen and has one or more groups selected from an ester group, an ether group and a carbonate group, and is more suitably one which contains an internal electron donor compound which contains magnesium, titanium and a halogen and has one or more groups selected from an ester group, an ether group and a carbonate group and does not have an aromatic ring structure directly bonded to a carboxylate residue.
[0019] Examples of such a solid catalyst component (A) include those obtained by mutually contacting a magnesium compound (a), a titanium halogen compound (b), and an internal electron donor compound (c) which has one or more groups selected from an ester group, an ether group, and a carbonate group and does not have an aromatic ring structure; and those obtained by mutually contacting a magnesium compound (a), a titanium halogen compound (b), and an internal electron donor compound (c) which has one or more groups selected from an ester group, an ether group, and a carbonate group, and does not have an aromatic ring structure directly bonded to a carboxylate residue.
[0020] The magnesium compound (a) may be at least one selected from magnesium dihalides, dialkyl magnesium, alkyl magnesium halides, dialkoxy magnesium, diaryloxy magnesium, alkoxy magnesium halides, fatty acid magnesium, and the like. Among these magnesium compounds, magnesium dihalides, mixtures of magnesium dihalides and dialkoxymagnesium, and dialkoxymagnesium are preferred, with dialkoxymagnesium being particularly preferred.
[0021] Specific examples of the dialkoxymagnesium include one or more selected from dimethoxymagnesium, diethoxymagnesium, dipropoxymagnesium, dibutoxymagnesium, ethoxymethoxymagnesium, ethoxypropoxymagnesium, butoxyethoxymagnesium, and the like. Of these, diethoxymagnesium is particularly preferred.
[0022] The dialkoxymagnesium may be a commercially available product, or may be one obtained by reacting metallic magnesium with an alcohol in the presence of a halogen-containing organometallic compound or the like.
[0023] The dialkoxymagnesium may be granular or powdery, and may be amorphous or spherical. For example, when a spherical dialkoxymagnesium is used, a polymer powder having a better particle shape and a narrow particle size distribution is easily obtained, the handling of the polymer powder (produced polymer powder) produced by polymerization is improved, and problems such as clogging of the filter in the polymer separation device caused by fine powder contained in the produced polymer powder are easily solved. The spherical dialkoxymagnesium does not necessarily have to be perfectly spherical, and may be elliptical or potato-shaped.
[0024] The dialkoxymagnesiums may be used alone or in combination of two or more kinds.
[0025] Furthermore, the dialkoxymagnesium preferably has an average particle size (average particle size D50) of 1 to 200 μm, more preferably 5 to 150 μm, where average D50 refers to the particle size at 50% of the cumulative particle size in the volume cumulative particle size distribution measured using a laser light scattering diffraction particle size measuring device.
[0026] When the dialkoxymagnesium is spherical, the average particle size is preferably from 1 to 100 μm, more preferably from 5 to 80 μm, and even more preferably from 10 to 70 μm.
[0027] The dialkoxymagnesium preferably has a narrow particle size distribution with little fine or coarse powder.
[0028] Specifically, when measured using a laser light scattering diffraction method particle size measuring instrument, the dialkoxymagnesium preferably contains 20% or less particles (fine powder) with a particle size of 5 μm or less, more preferably 10% or less, while when measured using a laser light scattering diffraction method particle size measuring instrument, the dialkoxymagnesium preferably contains 10% or less particles (coarse powder) with a particle size of 100 μm or more, more preferably 5% or less.
[0029] Furthermore, the dialkoxymagnesium preferably has a particle size distribution represented by the formula "ln(D90 / D10)" of 3 or less, and more preferably 2 or less. In the present invention, a dialkoxymagnesium having a particle size distribution represented by the above formula "ln(D90 / D10)" that is equal to or smaller than the above-mentioned predetermined value means "one having a narrow particle size distribution". Here, D90 means a particle size of 90% of the integrated particle size in the volumetric integrated particle size distribution when measured using a laser light scattering diffraction particle size measuring instrument, and D10 means a particle size of 10% of the integrated particle size in the volumetric integrated particle size distribution when measured using a laser light scattering diffraction particle size measuring instrument.
[0030] Methods for producing the above-mentioned spherical dialkoxymagnesium are exemplified in, for example, JP-A-58-4132, JP-A-62-51633, JP-A-3-74341, JP-A-4-368391, JP-A-8-73388 and the like.
[0031] The titanium halogen compound (b) is not particularly limited, but may be represented by the following general formula (II): Ti(OR 2 ) i X 4-i (II) (In the formula, R 2represents an alkyl group having 1 to 4 carbon atoms, X represents a halogen atom such as a chlorine atom, a bromine atom, or an iodine atom, and i is an integer of 0 to 3. It is preferable that the titanium tetrahalide or alkoxy titanium halide is one of the compounds selected from the group consisting of titanium tetrahalides and alkoxy titanium halides represented by the following formula:
[0032] As the titanium halogen compound (b) represented by the above general formula (II), specifically, titanium tetrahalides include titanium tetrahalides such as titanium tetrachloride, titanium tetrabromide, and titanium tetraiodide.Alkoxy titanium halides include methoxy titanium trichloride, ethoxy titanium trichloride, propoxy titanium trichloride, n-butoxy titanium trichloride, dimethoxy titanium dichloride, diethoxy titanium dichloride, dipropoxy titanium dichloride, di-n-butoxy titanium dichloride, trimethoxy titanium chloride, triethoxy titanium chloride, tripropoxy titanium chloride, and tri-n-butoxy titanium chloride.Of these, titanium tetrahalides are preferred, and titanium tetrachloride is more preferred.
[0033] The internal electron donor compound (c) having one or more groups selected from an ester group, an ether group, and a carbonate group, and the internal electron donor compound (c) having one or more groups selected from an ester group, an ether group, and a carbonate group and not having an aromatic ring structure directly bonded to a carboxylate residue, which are used as the electron donor compound in the solid catalyst component (A), are not particularly limited.
[0034] The above-mentioned internal electron donor compound (c) having one or more groups selected from an ester group, an ether group, and a carbonate group and not having an aromatic ring structure directly bonded to a carboxylate residue is used in the present invention as a specific internal electron donor compound not having an aromatic ring structure directly bonded to a carboxylate residue.
[0035] When the internal electron donor compound (c) is a compound having an ester group, it is preferably a compound having 1 to 3 ester residues, and examples of the compound include one or more selected from monocarboxylic acid esters having one ester residue, dicarboxylic acid diesters having two ester residues, polycarboxylic acid polyesters having three or more ester residues, ether-carboxylic acid esters having one ester residue and one alkoxy group, and diol esters.
[0036] Specific examples of the internal electron donor compound (c) having an ester group include monocarboxylic acid esters such as acetate, propionate, benzoate, p-toluate, and anisate; succinate diesters, malonate diesters, maleate diesters, cyclohexene carboxylate diesters, 2,3-dialkyl succinate diesters, benzylidene malonate diesters, cyclohexane-1,2-dicarboxylate diesters, 1-cyclohexene-1,2-dicarboxylate diesters, 4-methylcyclohexane-1,2-dicarboxylate diesters, 3-methylcyclohexane-1,2-dicarboxylate diesters, 3,6-diphenylcyclohexane-1,2-dicarboxylate diesters, 3-methyl-6-n-propenoate diesters, and the like. dicarboxylic acid diesters such as ethyl 3-ethoxy-2-isopropylpropionate, ethyl 3-ethoxy-2-isobutylpropionate, ethyl 3-ethoxy-2-t-butylpropionate, ethyl 3-ethoxy-2-t-pentylpropionate, ethyl 3-ethoxy-2-cyclohexylpropionate, ethyl 3-ethoxy-2-cyclopentylpropionate, and the like; and diol esters such as 2,4-pentanediol dibenzoate, 3-methyl-2,4-pentanediol dibenzoate, 3-methyl-5-t-butyl-1,2-phenylenedibenzoate, 3,5-diisopropyl-1,2-phenylenedibenzoate, and the like are preferred. Among these, particularly preferred are one or more selected from diethyl maleate, diethyl benzylidenemalonate, diethyl cyclohexane-1,2-dicarboxylate, di-n-propyl cyclohexane-1,2-dicarboxylate, di-n-butyl cyclohexane-1,2-dicarboxylate, ethyl 3-ethoxy-2-isopropylpropionate, ethyl 3-ethoxy-2-t-butylpropionate, ethyl 3-ethoxy-2-t-pentylpropionate, 2,4-pentanediol dibenzoate, 3-methyl-2,4-pentanediol dibenzoate, 3-methyl-5-t-butyl-1,2-phenylene dibenzoate, and 3,5-diisopropyl-1,2-phenylene dibenzoate.
[0037] When the internal electron donor compound (c) is a compound having an ether group, it is preferably a compound having one ether group, a compound having a fluorene structure, or a compound having a diether structure having 1 to 2 alkyl or cycloalkyl groups having 3 to 7 carbon atoms. Among these, a 1,3-diether compound having a structure in which ether groups are bonded to the 1,3-positions of a propane skeleton (1,3-dialkoxypropane structure) and which may further contain desired substituents is more preferred.
[0038] Specific examples of the internal electron donor compound (c) having an ether group include monoethers such as methyl ether, ethyl ether, propyl ether, butyl ether, and amyl ether, and diethers such as diphenyl ether, 2,2-dialkyl-1,3-dialkoxypropane, 2,2-dicycloalkyl-1,3-dimethoxypropane, and 9,9-bis(methoxymethyl)fluorene. Among these, ether carboxylates are preferred.
[0039] Among the above, particularly preferred are 2-isopropyl-2-isobutyl-1,3-dimethoxypropane, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane and 9,9-bis(methoxymethyl)fluorene.
[0040] When the internal electron donor compound (c) is a compound having a carbonate group, it is preferably a compound having 1 to 3 carbonate groups.Specific examples of such compounds include a carbonate-ether compound having one carbonate group and one alkoxy group, a carbonate-ester compound having one carbonate group and one ester residue, a compound having one carbonate group and one carboxyl group, a dicarbonate having two carbonate groups, and a polycarbonate having three or more carbonate groups. Among these, carbonate ethers, carbonate esters and dicarbonates are preferred, and particularly preferred are (2-ethoxyethyl)methyl carbonate, (2-ethoxyethyl)ethyl carbonate, (2-propoxyethyl)methyl carbonate, (2-benzyloxyethyl)phenyl carbonate, and 5-t-butyl-1,2-phenylenediphenyl dicarbonate.
[0041] As the internal electron donor compound (c), at least one compound selected from the group consisting of 1,3-diether compounds, carbonate-ether compounds and carboxylic acid diester compounds is particularly preferred.
[0042] The solid catalyst component (A) is preferably prepared by contacting the above-mentioned magnesium compound (a), the above-mentioned titanium halogen compound (b), and the above-mentioned internal electron donor compound (c) with, if necessary, a polysiloxane, in the presence of an inert organic solvent.
[0043] The polysiloxane is a polymer having a siloxane bond (-Si-O bond) in the main chain, and is also collectively called silicone oil. It has a viscosity of 0.02 to 100.00 cm at 25°C. 2 / s (2 to 1,000 centistokes) that is liquid or viscous at room temperature.
[0044] Examples of the chain polysiloxane include dimethylpolysiloxane and methylphenylpolysiloxane. Examples of the partially hydrogenated polysiloxane include methylhydrogenpolysiloxane with a hydrogenation rate of 10 to 80%. Examples of the cyclic polysiloxane include hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentanesiloxane, 2,4,6-trimethylcyclotrisiloxane, and 2,4,6,8-tetramethylcyclotetrasiloxane. Examples of the modified polysiloxane include higher fatty acid group-substituted dimethylsiloxane, epoxy group-substituted dimethylsiloxane, and polyoxyalkylene group-substituted dimethylsiloxane. Among these, decamethylcyclopentasiloxane and dimethylpolysiloxane are preferred, and decamethylcyclopentasiloxane is particularly preferred.
[0045] By contacting with polysiloxane, the stereoregularity or crystallinity of the resulting polymer can be easily improved, and furthermore, the amount of fine powder in the resulting polymer can be easily reduced.
[0046] The inert organic solvent is preferably one that dissolves the titanium halide compound (b) but does not dissolve the magnesium compound (a).Specific examples of the inert organic solvent include saturated hydrocarbon compounds such as pentane, hexane, heptane, octane, nonane, decane, cyclohexane, methylcyclohexane, ethylcyclohexane, 1,2-diethylcyclohexane, methylcyclohexene, decalin, and mineral oil; aromatic hydrocarbon compounds such as benzene, toluene, xylene, and ethylbenzene; and halogenated hydrocarbon compounds such as orthodichlorobenzene, methylene chloride, 1,2-dichlorobenzene, carbon tetrachloride, and dichloroethane.
[0047] The inert organic solvent is preferably a saturated hydrocarbon compound or an aromatic hydrocarbon compound that is liquid at room temperature and has a boiling point of 50 to 300° C. Among these, one or more selected from hexane, heptane, octane, cyclohexane, ethylcyclohexane, decalin, mineral oil, toluene, xylene, and ethylbenzene are preferred.
[0048] The solid catalyst component (A) can be prepared, for example, by suspending the magnesium compound (a) and the internal electron donor compound (c) in an inert organic solvent to form a suspension, and then contacting a mixed solution formed from the titanium halide compound (b) and the inert organic solvent with the suspension to cause a reaction.
[0049] Also, as a method for preparing the solid catalyst component (A), there can be mentioned a preparation method in which a magnesium compound (a) is suspended in a titanium halide compound (b) or an inert organic solvent, and then contacted with an internal electron donor compound (c) and, if necessary, a titanium halide compound (b) to cause a reaction.
[0050] In the process for producing a catalyst for olefin polymerization according to the present invention, when the solid catalyst component (A) is prepared by contacting each component with each other, the process can be carried out in an inert gas atmosphere.
[0051] Specifically, the components are contacted with each other in an inert gas atmosphere in a vessel equipped with a stirrer under conditions where moisture and the like have been removed, while being stirred, and then reacted at a predetermined temperature to obtain the solid catalyst component (A).
[0052] The temperature at which the components are contacted may be in a relatively low range around room temperature when the components are simply contacted and mixed by stirring, or when the components are dispersed or suspended to carry out a modification treatment.
[0053] When the components are contacted and then reacted to obtain a product, the temperature range is preferably 40 to 130° C., and in this case, it is preferable to maintain the components at the same temperature after contacting them to react them.
[0054] If the temperature at which the above-mentioned product is obtained is less than 40° C., the reaction does not proceed sufficiently, and the resulting solid catalyst component is unlikely to exhibit sufficient performance. If the temperature exceeds 130° C., the solvent used will evaporate significantly, making it difficult to control the reaction.
[0055] The reaction time for obtaining the above product is preferably 1 minute or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more.
[0056] The ratio of the amounts of the respective components used in preparing the solid catalyst component (A) varies depending on the preparation method, and may be appropriately determined.
[0057] When preparing the solid catalyst component (A), the titanium halide compound (b) is contacted in an amount of preferably 0.50 to 100.00 mol, more preferably 0.50 to 10.00 mol, and even more preferably 1.00 to 5.00 mol per 1.00 mol of the magnesium compound (a).
[0058] In addition, when preparing the catalyst component, the internal electron donor compound (c) is preferably contacted in an amount of 0.01 to 10.00 mol, more preferably 0.01 to 1.00 mol, and even more preferably 0.02 to 0.6 mol, per 1.00 mol of the magnesium compound (a).
[0059] When polysiloxane is used in preparing the solid catalyst component (A), the amount of polysiloxane contacted is preferably 0.01 to 100.00 g, more preferably 0.05 to 80.00 g, and even more preferably 1.00 to 50.00 g, per 1.00 mol of the magnesium compound (a).
[0060] When an inert organic solvent such as an aromatic hydrocarbon compound is used during preparation of the solid catalyst component (A), the amount of the organic solvent used is preferably 0.001 to 500,000 mol, more preferably 0.001 to 70,000 mol, and even more preferably 0.005 to 50,000 mol, per 1,000 mol of the magnesium compound (a).
[0061] In the process for producing an olefin polymerization catalyst according to the present invention, the contents of titanium atoms, magnesium atoms, halogen atoms and electron donor compounds constituting the solid catalyst component (A) are not particularly limited as long as the effects of the present invention can be exhibited.
[0062] The solid catalyst component (A) preferably contains titanium atoms in an amount of 1.0 to 10.0 mass %, more preferably 1.5 to 8.0 mass %, and even more preferably 1.5 to 5.0 mass %.
[0063] The solid catalyst component (A) contains magnesium atoms in an amount of preferably 10.0 to 70.0 mass%, more preferably 10.0 to 50.0 mass%, even more preferably 15.0 to 40.0 mass%, and even more preferably 15.0 to 25.0 mass%.
[0064] The solid catalyst component (A) contains halogen atoms in an amount of preferably 20.0 to 90.0 mass %, more preferably 30.0 to 85.0 mass %, even more preferably 40.0 to 80.0 mass %, and still more preferably 45.0 to 80.0 mass %.
[0065] The solid catalyst component (A) contains the internal electron donor compound (c) in a total amount of preferably 0.5 to 30.0 mass %, more preferably 1.0 to 25.0 mass %, and further preferably 2.0 to 20.0 mass %.
[0066] In the present application, the titanium atom content and the magnesium atom content in the solid catalyst component (A) refer to values measured in accordance with the method (oxidation-reduction titration) described in JIS 8311-1997 "Method for determining titanium in titanium ore."
[0067] In this application, the content of halogen atoms contained in the solid catalyst component (A) of the present invention means a value measured by a silver nitrate titration method in which the solid catalyst component is treated with a mixed solution of sulfuric acid and pure water to prepare an aqueous solution, a predetermined amount is taken, and halogen atoms are titrated with a standard silver nitrate solution. The content of electron donor compound means a value measured by a gas chromatography FID (Flame Ionization Detector) method in which the solid catalyst is hydrolyzed, the internal electron donor is extracted with an aromatic solvent, and the solution is subjected to hydrolysis.
[0068] Particularly preferred methods for preparing the solid catalyst component (A) include the following methods.
[0069] First, a magnesium compound (a) is suspended in an aromatic hydrocarbon compound (inert organic solvent) having a boiling point of 50 to 150° C. to obtain a suspension. Next, the obtained suspension is contacted with a titanium halogen compound (b) to carry out a reaction treatment.
[0070] Before or after contacting the above suspension with the titanium halogen compound (b), one or more compounds selected from the internal electron donor compounds (c) are contacted at −20 to 130° C. If necessary, a polysiloxane is further contacted to carry out a reaction treatment.
[0071] In the above preparation method, it is desirable to carry out a maturation reaction at a low temperature before or after contacting with the electron donor compound (c).
[0072] In the method for producing a catalyst for olefin polymerization according to the present invention, the above-mentioned solid catalyst component (A) and a compound represented by the following general formula (I); R 1 p AlQ 3-p(I) (wherein R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is a real number satisfying 0 < p ≤ 3.) is brought into mutual contact with an organoaluminum compound (B) represented by
[0073] In the organoaluminum compound represented by the general formula (I), R 1 is an alkyl group having 1 to 6 carbon atoms, which may be linear or branched, and examples thereof include groups selected from a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, an isopentyl group, a hexyl group, and an isohexyl group, and an ethyl group or an isobutyl group is preferred.)
[0074] In the organoaluminum compound represented by the general formula (I), Q is a hydrogen atom or a halogen atom, and a hydrogen atom, a chlorine atom, or a bromine atom is preferred.)
[0075] Further, in the organoaluminum compound represented by the general formula (I), p is a real number satisfying 0 < p ≤ 3, a real number of 2 to 3 is preferred, and 2, 2.5, or 3 is more preferred.)
[0076] Specific examples of such an organoaluminum compound (B) include triethylaluminum, diethylaluminum chloride, triisobutylaluminum, diethylaluminum bromide, and diethylaluminum hydride, and one kind or two or more kinds can be used. Among these, triethylaluminum or triisobutylaluminum is preferred.)
[0077] In the method for producing an olefin polymerization catalyst according to the present invention, it is believed that the use of the specific organoaluminum compound (B) represented by the above general formula (I) improves the action of the organoaluminum compound (B) on the electron donor compound constituting the solid catalyst component (A), thereby optimally activating the solid catalyst component (A). In addition, when using a solid catalyst component (A) containing an internal electron donor compound (c) other than a phthalic acid ester, it is believed that even when the olefin polymerization catalyst is prepared in an inert gas atmosphere, it exhibits excellent catalytic activity during polymerization treatment and can produce an olefin polymer with excellent stereoregularity.
[0078] In the method for producing an olefin polymerization catalyst according to the present invention, at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) has been previously contacted with a hydrocarbon compound having one or more vinyl groups. That is, in the present application, the term "preliminary contact treatment with a hydrocarbon compound having one or more vinyl groups" means that, before the solid catalyst component (A) and the organoaluminum compound (B) are brought into contact with each other, at least one of them is brought into contact with a hydrocarbon compound having one or more vinyl groups.
[0079] In the method for producing a catalyst for olefin polymerization according to the present invention, the object to be contacted in advance with a hydrocarbon compound having one or more vinyl groups may be the solid catalyst component (A), the organoaluminum compound (B), or both the solid catalyst component (A) and the organoaluminum compound (B). That is, in the present invention, the solid catalyst component (A) and the organoaluminum compound (B) are previously contact-treated with a hydrocarbon compound having one or more vinyl groups, and then contact-treated with each other in the following three modes (1) to (3). (1) A solid catalyst component (A) is preliminarily contacted with a hydrocarbon compound having one or more vinyl groups, and then the preliminarily contacted product is contacted with an organoaluminum compound (B). (2) An organoaluminum compound (B) is preliminarily contacted with a hydrocarbon compound having one or more vinyl groups, and then the pre-contact product obtained is contacted with a solid catalyst component (A). (3) A solid catalyst component (A) is contacted in advance with a hydrocarbon compound having one or more vinyl groups to obtain a pre-contact product A, and an organoaluminum compound (B) is contacted in advance with a hydrocarbon compound having one or more vinyl groups to obtain a pre-contact product B, and the obtained pre-contact product A is contacted with the pre-contact product B.
[0080] In the method for producing an olefin polymerization catalyst according to the present invention, the amount of a hydrocarbon compound having one or more vinyl groups to be preliminarily contacted with at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) is preferably 1 mol or more, more preferably 1 to 1,000,000 mols, more preferably 10 to 100,000 mols, and even more preferably 100 to 50,000 mols, per mol of titanium constituting the solid catalyst component (A) used in the production of an olefin polymerization catalyst.
[0081] In addition, in the case where both the solid catalyst component (A) and the organoaluminum compound (B) have been previously contact-treated with a hydrocarbon compound having one or more vinyl groups, the above-mentioned contact amount means each of the contact amounts when the solid catalyst component (A) and the organoaluminum compound (B) are contact-treated with a hydrocarbon compound having one or more vinyl groups.
[0082] In the method for producing a catalyst for olefin polymerization according to the present invention, by controlling the amount of the hydrocarbon compound having one or more vinyl groups to be contacted in advance with at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) so as to satisfy the above-mentioned requirement, a protective film of polyolefin can be easily formed on the surface of at least one selected from the solid catalyst component (A) and the organoaluminum compound (B).
[0083] In the method for producing a catalyst for olefin polymerization according to the present invention, the hydrocarbon compound having one or more vinyl groups is not particularly limited, but is preferably one or more selected from ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1,4-hexadiene, 1,5-hexadiene, 1,6-octadiene, 1,7-octadiene, 1-heptene, 1-octene, vinylcyclohexane, and vinylcyclohexene, and more preferably one or more selected from ethylene, propylene, 1-hexene, 3-methyl-1-pentene, 1,5-hexadiene, and 4-methyl-1-pentene.
[0084] The hydrocarbon compound having one or more vinyl groups to be pre-contacted with the solid catalyst component (A) and the organoaluminum compound (B) may be the same as or different from the olefins to be polymerized by the olefin polymerization catalyst of the present invention.
[0085] In the method for producing a catalyst for olefin polymerization according to the present invention, the concentration of the hydrocarbon compound having one or more vinyl groups in the organic solvent is preferably 0.0001 to 500 mol / L, more preferably 0.001 to 50 mol / L, and further preferably 0.01 to 5 mol / L.
[0086] In the method for producing a catalyst for olefin polymerization according to the present invention, it is preferred that either one of the solid catalyst component (A) or the organoaluminum compound (B) is preliminarily contacted with a hydrocarbon compound having one or more vinyl groups in an organic solvent, and then the resulting mixture is contacted with the other.
[0087] In the method for producing an olefin polymerization catalyst according to the present invention, the embodiment in which at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) is contacted in advance with a hydrocarbon compound having one or more vinyl groups is not particularly limited. When the hydrocarbon compound having one or more vinyl groups is in a liquid state, the solid catalyst component (A) or the organoaluminum compound (B) may be immersed in the hydrocarbon compound having one or more vinyl groups, or the hydrocarbon compound having one or more vinyl groups may be applied to the solid catalyst component (A) or the organoaluminum compound (B). When the hydrocarbon compound having one or more vinyl groups is in a gaseous state, the solid catalyst component (A) or the organoaluminum compound (B) may be maintained in an atmosphere of the hydrocarbon compound having one or more vinyl groups.
[0088] A specific embodiment of the preliminarily contacting at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) with a hydrocarbon compound having one or more vinyl groups may include a method in which a predetermined amount of the solid catalyst component (A) or the organoaluminum compound (B) to be contacted is mixed in a vessel containing a predetermined amount of a hydrocarbon compound having one or more vinyl groups.
[0089] When the hydrocarbon compound having one or more vinyl groups is contacted in advance with both the solid catalyst component (A) and the organoaluminum compound (B), a predetermined amount of either the solid catalyst component (A) or the organoaluminum compound (B) to be contacted may be mixed in a plurality of vessels each containing a predetermined amount of the hydrocarbon compound having one or more vinyl groups.
[0090] In the method for producing an olefin polymerization catalyst according to the present invention, when a hydrocarbon compound having one or more vinyl groups is contacted in advance with at least one selected from the solid catalyst component (A) and the organoaluminum compound (B), the contact time is preferably 15 seconds or more, more preferably 1 to 300 minutes, and even more preferably 1 to 60 minutes.
[0091] In the method for producing an olefin polymerization catalyst according to the present invention, when at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) is contacted in advance with a hydrocarbon compound having one or more vinyl groups, the contact temperature is preferably 0 to 80°C, more preferably 10 to 60°C, and even more preferably 20 to 50°C.
[0092] In the method for producing an olefin polymerization catalyst according to the present invention, the solid catalyst component (A) or the organoaluminum compound (B) is usually subjected to the production of an olefin polymerization catalyst in a state of contact with a hydrocarbon compound having one or more vinyl groups (together with a hydrocarbon compound having one or more vinyl groups).
[0093] When the hydrocarbon compound having one or more vinyl groups is liquid at room temperature, the solid catalyst component (A) or the organoaluminum compound (B) may be isolated from the hydrocarbon compound having one or more vinyl groups and then used in the production of a catalyst for olefin polymerization.
[0094] The solid catalyst component (A) or the organoaluminum compound (B) previously subjected to contact treatment with a hydrocarbon compound having one or more vinyl groups is preferably subjected to a reaction with a catalyst for olefin polymerization within 24 hours after the above contact treatment, and more preferably subjected to a reaction with a catalyst for olefin polymerization immediately after the above contact treatment.
[0095] In the method for producing an olefin polymerization catalyst according to the present invention, it is believed that a protective film of polyolefin can be easily formed on the surface of at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) by previously contacting at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) with a hydrocarbon compound having one or more vinyl groups.
[0096] As a result, it is believed that excessive activation reaction of the titanium active sites in the solid catalyst component (A) by the organoaluminum compound (B) can be suppressed, and the catalyst for olefin polymerization can be supplied to the polymerization reaction in a stable state while suppressing deactivation.
[0097] Therefore, according to the present invention, even when a solid catalyst component containing an internal electron donor compound not having an aromatic ring structure directly bonded to a carboxylate residue is used instead of an internal electron donor compound having an aromatic ring structure directly bonded to a carboxylate residue, the catalyst exhibits excellent catalytic activity during polymerization of olefins by suppressing a decrease in polymerization activity due to early deactivation of active sites after catalyst formation, and an olefin polymer having excellent stereoregularity can be easily produced.
[0098] In the method for producing an olefin polymerization catalyst according to the present invention, the solid catalyst component (A) and the organoaluminum compound (B) may be contacted with each other in the presence of an external electron donor compound (C) or in the absence of an external electron donor compound (C).
[0099] When the contact of the solid catalyst component (A) with the organoaluminum compound (B) is carried out in the absence of the external electron-donor compound (C), it is preferred that after the solid catalyst component (A) and the organoaluminum compound (B) are contacted with each other, the contact product thus obtained is further contacted with the external electron-donor compound (C).
[0100] In the method for producing a catalyst for olefin polymerization according to the present invention, examples of the external electron donor compound (C) include the same as the internal electron donor compound (c) constituting the above-mentioned solid catalyst component (A) and organosilicon compounds, and among these, one or more compounds having one or more groups selected from a carbonate group, an ether group and an ester group and organosilicon compounds are preferred.
[0101] When the external electron donor compound is a compound having a carbonate group, it is preferably one or more selected from 2-ethoxyethyl phenyl carbonate, 2-benzyloxyethyl phenyl carbonate, and 2-ethoxyethyl-1-methyl carbonate.
[0102] When the external electron donor compound is a compound having an ether group, 1,3 diether is preferred, and in particular, one or more selected from 9,9-bis(methoxymethyl)fluorene and 2-isopropyl-2-isopentyl-1,3-dimethoxypropane are preferred.
[0103] When the external electron donor compound is a compound having an ester group, it is preferably at least one selected from methyl benzoate and ethyl benzoate.
[0104] When the external electron donor compound is an organosilicon compound, it is preferably at least one selected from organosilicon compounds containing a Si-OC bond and organosilicon compounds containing a Si-NC bond.
[0105] The organosilicon compound is represented by the following general formula (III): R 3 r Si(NR 4 R 5 ) s (OR 6 ) 4-(r+s) (III) (In the formula, r is an integer of 0≦r≦4, s is an integer of 0≦s≦4, and r+s is an integer of 0≦r+s≦4. 3 , R 4 and R 5 R is one selected from a hydrogen atom, a linear alkyl group having 1 to 12 carbon atoms, a branched alkyl group having 3 to 12 carbon atoms, a vinyl group, an allyl group, a substituted or unsubstituted cycloalkyl group, a phenyl group, and an aralkyl group. 3 , R 4 and R 5 R may contain a heteroatom. 3 , R 4 and R 5may be the same or different. 4 and R 5 may be bonded to form a ring. 6 R is one selected from an alkyl group having 1 to 4 carbon atoms, a vinyl group, an allyl group, a cycloalkyl group having 3 to 12 carbon atoms, a phenyl group having 6 to 12 carbon atoms, and an aralkyl group. 6 may contain a heteroatom.
[0106] In the above general formula (III), R 3 As the alkyl group, a linear alkyl group having 1 to 10 carbon atoms, a branched alkyl group having 3 to 10 carbon atoms, or a cycloalkyl group having 5 to 8 carbon atoms is preferable, and a linear alkyl group having 1 to 8 carbon atoms, a branched alkyl group having 3 to 8 carbon atoms, or a cycloalkyl group having 5 to 8 carbon atoms is particularly preferable.
[0107] In addition, in the above general formula (III), R 4 and R 5 As R, a linear alkyl group having 1 to 10 carbon atoms, a branched alkyl group having 3 to 10 carbon atoms, or a cycloalkyl group having 5 to 8 carbon atoms is preferable, and a linear alkyl group having 1 to 8 carbon atoms, a branched alkyl group having 3 to 8 carbon atoms, or a cycloalkyl group having 5 to 7 carbon atoms is particularly preferable. 4 and R 5 may be linked together to form a ring shape, in which case a ring shape is formed (NR 4 R 5 ) groups include a perhydroquinolino group and a perhydroisoquinolino group.
[0108] In the above general formula (III), R 6 is any one selected from an alkyl group, a cycloalkyl group, a phenyl group, a vinyl group, an allyl group, and an aralkyl group having 1 to 4 carbon atoms, preferably a linear alkyl group having 1 to 6 carbon atoms, or a branched alkyl group having 3 to 6 carbon atoms, and particularly preferably a linear alkyl group having 1 to 4 carbon atoms, or a branched alkyl group having 3 to 4 carbon atoms.
[0109] Examples of the external electron donor compound represented by the above general formula (III) include one or more compounds selected from phenylalkoxysilanes, alkylalkoxysilanes, phenylalkylalkoxysilanes, cycloalkylalkoxysilanes, cycloalkyl(alkyl)alkoxysilanes, (alkylamino)alkoxysilanes, alkyl(alkylamino)alkoxysilanes, alkyl(alkylamino)silanes, alkylaminosilanes, and the like. Of these, one or more selected from phenyltrimethoxysilane, t-butylmethyldimethoxysilane, t-butylethyldimethoxysilane, diisopropyldimethoxysilane, isopropylisobutyldimethoxysilane, diisopentyldimethoxysilane, diphenyldimethoxysilane, dicyclopentyldimethoxysilane, cyclohexylmethyldimethoxysilane, tetramethoxysilane, tetraethoxysilane, t-butylmethylbis(ethylamino)silane, bis(ethylamino)dicyclohexylsilane, dicyclopentylbis(ethylamino)silane, bis(perhydroquinolino)dimethoxysilane, bis(perhydroisoquinolino)dimethoxysilane, and diethylaminotriethoxysilane are preferably used.
[0110] The external electron donor compounds (C) may be used alone or in combination of two or more.
[0111] In the method for producing an olefin polymerization catalyst according to the present invention, the contact amount of the organoaluminum compound (B) during the formation of the polymerization catalyst is preferably 0.1 to 1000.0 mol, more preferably 1.0 to 800.0 mol, and further preferably 20.0 to 600.0 mol per 1.0 mol of titanium atom in the solid catalyst component (A).
[0112] In the method for producing an olefin polymerization catalyst according to the present invention, when an external electron donor compound (C) is used during the formation of the polymerization catalyst, the contact amount of the external electron donor compound (C) is preferably 0.005 to 1.000 mol, more preferably 0.080 to 0.500 mol, and even more preferably 0.010 to 0.300 mol per 1 mol of the organoaluminum compound (B) represented by general formula (I).
[0113] In the method for producing an olefin polymerization catalyst according to the present invention, the inert gas concentration in the atmosphere during preparation of the polymerization catalyst is preferably 0.0 to 1.0 mol / L, more preferably 0.0 to 0.5 mol / L, and even more preferably 0.0 to 0.1 mol / L.
[0114] The inert gas may be at least one selected from the group consisting of nitrogen gas, helium gas, neon gas, and argon gas.
[0115] In the method for producing an olefin polymerization catalyst according to the present invention, the polymerization catalyst may be produced in the presence of the olefin to be polymerized, or may be produced in the absence of the olefin to be polymerized.
[0116] In the method for producing an olefin polymerization catalyst according to the present invention, the temperature at which the solid catalyst component (A) and the organoaluminum compound (B) are contacted during preparation of the polymerization catalyst is preferably 40°C or lower, more preferably 0°C to 40°C, even more preferably 10°C to 40°C, and particularly preferably 10°C to 20°C.
[0117] In the method for producing an olefin polymerization catalyst according to the present invention, the treatment time for contacting the solid catalyst component (A) with the organoaluminum compound (B) is preferably from 10 seconds to 60 minutes, more preferably from 30 seconds to 30 minutes, even more preferably from 1 minute to 30 minutes, and particularly preferably from 1 minute to 10 minutes.
[0118] In preparing the above-mentioned polymerization catalyst, when the solid catalyst component (A) is contacted with the organoaluminum compound (B) and, if necessary, with the external electron donor compound (C), a reaction is instantly initiated to form the desired olefin polymerization catalyst.
[0119] Usually, when a solid catalyst component is contacted with an organoaluminum compound as a promoter and, if necessary, with an external electron-donor compound, the reaction proceeds rapidly, resulting in elimination of the internal electron-donor compound constituting the solid catalyst component and exchange with the external electron-donor compound, and activation of the solid catalyst component by the organoaluminum compound as a promoter. Particularly in an inert gas atmosphere, the catalytic active sites (titanium active sites) are likely to be deactivated due to excessive reaction.
[0120] In the method for producing a catalyst for olefin polymerization according to the present invention, at least one selected from the solid catalyst component (A) containing an internal electron donor compound and the organoaluminum compound (B) is previously contacted with a hydrocarbon compound having one or more vinyl groups, so that a protective film of polyolefin is easily formed on the surface of the solid catalyst component. As a result, it is considered that the excessive activation reaction of the titanium active site in the solid catalyst component by the organoaluminum compound is suppressed, and the catalyst for olefin polymerization can be stably used for polymerization reaction while suppressing deactivation.
[0121] Therefore, according to the present invention, a method for producing a catalyst for olefin polymerization can be provided which exhibits excellent catalytic activity during olefin polymerization by suppressing a decrease in polymerization activity due to early deactivation of active sites after catalyst formation, and is capable of producing olefin polymers with excellent stereoregularity.
[0122] In the production process according to the present invention, the desired olefin polymerization catalyst can be prepared by the above contact treatment.
[0123] <Catalyst for olefin polymerization> The catalyst for olefin polymerization according to the present invention comprises a solid catalyst component (A) containing magnesium, titanium, a halogen and an internal electron donor compound; The following general formula (I); R 1 p AlQ 3-p (I) (In the formula, R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is a real number satisfying 0 < p ≤ 3.) and an organoaluminum compound (B) represented by a hydrocarbon compound having one or more vinyl groups, and the hydrocarbon compound having one or more vinyl groups is contained in an amount of at least 0.1% by mass based on the total weight of titanium contained in the solid catalyst component (A). It is characterized by this.
[0124] In the olefin polymerization catalyst according to the present invention, the content of the hydrocarbon compound having one or more vinyl groups is a mass ratio to the total weight of titanium contained in the solid catalyst component (A), which is defined by the following formula (α), and is at least 0.1% by mass (0.1% by mass or more), preferably 0.1 to 800.0% by mass, more preferably 0.5 to 775.0% by mass, and even more preferably 0.8 to 750.0% by mass. Content ratio (%) of the hydrocarbon compound having one or more vinyl groups = {Content (mass%) of the hydrocarbon compound having one or more vinyl groups / Total content ratio (mass%) of titanium contained in the solid catalyst component (A)} × 100 (α)
[0125] In the present application documents, the content of the hydrocarbon compound having one or more vinyl groups in the olefin polymerization catalyst means a value obtained by weighing about 1 g of the olefin polymerization catalyst from which the solvent component has been removed in advance, hydrolyzing it in a mixed solution of 5 mL of 10% hydrochloric acid and 45 mL of absolute ethanol for 15 minutes, and then recovering the solid (hydrocarbon compound having a vinyl group) using a pre-weighed filter paper (Whatman 2V Filter), rinsing it with distilled water to remove the hydrochloric acid component, and weighing it after air-drying until a constant weight is reached, according to the following formula. Content of hydrocarbon compounds having one or more vinyl groups (mass%)={weight of solid matter w(g) / (weight of catalyst for olefin polymerization (g)-weight of solid matter w(g))}×100
[0126] In the olefin polymerization catalyst according to the present invention, the details of the solid catalyst component (A), the organoaluminum compound (B) and the hydrocarbon compound having one or more vinyl groups are the same as those described above.
[0127] The olefin polymerization catalyst according to the present invention can be suitably produced by the above-mentioned method for producing an olefin polymerization catalyst according to the present invention.
[0128] According to the present invention, it is possible to provide an olefin polymerization catalyst which exhibits excellent catalytic activity during olefin polymerization by suppressing a decrease in polymerization activity due to early deactivation of active sites after catalyst formation, and which is capable of producing olefin polymers having excellent stereoregularity.
[0129] <Method of producing olefin polymer> Next, the process for producing the olefin polymer according to the present invention will be described. The present invention relates to a method for producing an olefin polymer, which is characterized in that olefins are polymerized using the olefin polymerization catalyst obtained by the production method according to the present invention or the olefin polymerization catalyst according to the present invention.
[0130] When olefins are polymerized using the polymerization catalyst obtained by the production method according to the present invention or the polymerization catalyst according to the present invention, the polymerization catalyst can be prepared, isolated, and then contacted with olefins, or the polymerization catalyst can be prepared, and then directly (without isolation) brought into contact with olefins for polymerization treatment.
[0131] The polymerization of olefins may be homopolymerization or copolymerization of olefins, and may be random copolymerization or block copolymerization.
[0132] Examples of olefins to be polymerized include one or more selected from ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, vinylcyclohexane, 1-hexene, 1,5-hexadiene, and the like. Among these, ethylene, propylene, 4-methyl-1-pentene, 1-hexene, and 1,5-hexadiene are preferred, and ethylene and propylene are particularly preferred.
[0133] When olefins are copolymerized, for example, when propylene is copolymerized with an olefin other than propylene, the olefin copolymerized with propylene may be one or more selected from ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, vinylcyclohexane, etc., and particularly, ethylene and 1-butene are preferred.
[0134] For example, when propylene is copolymerized with other olefins, examples of the copolymerization include random copolymerization in which propylene and a small amount of ethylene are polymerized as comonomers in one stage, and so-called propylene-ethylene block copolymerization in which propylene is homopolymerized in a first stage (first polymerization tank) and propylene and ethylene are copolymerized in a second stage (second polymerization tank) or multiple stages (multistage polymerization tank).
[0135] The polymerization temperature of the olefins is preferably from room temperature to 200° C., more preferably from room temperature to 100° C. Here, room temperature means 20° C.
[0136] The polymerization pressure for the olefins is preferably 10 MPa or less, and more preferably 6 MPa or less.
[0137] The olefins may be polymerized by a continuous polymerization method or a batch polymerization method. Furthermore, the polymerization reaction may be carried out in one stage or in two or more stages.
[0138] When the polymerization reaction of the olefins is carried out, the polymerization atmosphere may be either an inert gas atmosphere or a gas atmosphere of the olefins to be polymerized, such as propylene.
[0139] According to the process for producing an olefin polymer according to the present invention, after formation of a catalyst, a decrease in polymerization activity due to early deactivation of active sites is suppressed, thereby exhibiting excellent catalytic activity during polymerization of olefins, and an olefin polymer having excellent stereoregularity can be easily produced.
[0140] (Example) EXAMPLES Next, the present invention will be described more specifically with reference to examples and comparative examples, but the present invention is not limited to the following examples in any way.
[0141] (Production Example 1) <Preparation of solid catalyst component> The inside of a 500 mL round-bottom flask equipped with a stirrer was thoroughly purged with nitrogen gas, and 20 g of diethoxymagnesium and 80 mL of toluene were placed in the round-bottom flask to obtain a diethoxymagnesium-containing liquid suspension.
[0142] Next, the inside of a 500 mL round-bottom flask equipped with a stirrer was thoroughly replaced with nitrogen gas, and 60 mL of toluene and 40 mL of titanium tetrachloride were added to the round-bottom flask to obtain a mixed solution of these. Next, the diethoxymagnesium-containing liquid was added to this toluene-titanium tetrachloride mixed solution to form a suspension.
[0143] Next, the obtained suspension was reacted at -6°C for 1 hour, and then, while the temperature of the suspension was rising, 6.4 mL (31.6 mmol) of 1-cyclohexene-1,2-dicarboxylate diethyl (CHDCDE) was added as an internal electron donor compound, and the suspension was reacted at 105°C for 1.5 hours while being stirred.
[0144] After the reaction was completed, the supernatant was removed from the suspension to obtain a precipitate, which was then washed four times with 190 mL of toluene at 100° C. to obtain a reaction product. 30 mL of titanium tetrachloride and 90 mL of toluene were added to the reaction product, and the mixture was heated to 105° C. and reacted for 15 minutes to obtain a reaction product. After repeating this process three times, the reaction product was washed six times with 150 mL of n-heptane at 40° C. and subjected to solid-liquid separation to obtain a solid catalyst component (solid catalyst component (A1)).
[0145] The titanium atom content in the obtained solid catalyst component (A1) was measured and found to be 2.0 mass %. The content of titanium atoms in the solid catalyst component (A1) was measured according to the method (oxidation-reduction titration) described in JIS 8311-1997 "Method for determining titanium in titanium ore" (the same applies to the following production examples).
[0146] Example 1 <Formation of polymerization catalyst> The atmosphere inside a 2.0-liter autoclave equipped with a stirrer (propylene concentration: 0.04 mol / L) was replaced with propylene gas (olefins), and 0.003 millimole, calculated as titanium atom, of the solid catalyst component (A1) obtained in Production Example 1 was charged into the autoclave (preliminarily contacted with 27 kilomoles of propylene gas per mole of titanium constituting the solid catalyst component (A1)), and the autoclave was maintained at 20° C. for 1 minute.
[0147] Next, 2.4 mmol of triethylaluminum (organoaluminum compound (B)) and 0.24 mmol of cyclohexylmethyldimethoxysilane (CMDMS) (external electron donor compound (C)) were charged into the autoclave, and the internal temperature of the autoclave was maintained at 20° C. for 1 minute to prepare a polymerization catalyst.
[0148] <Production of ethylene-propylene block copolymer> 15 moles of liquefied propylene and 0.20 MPa (partial pressure) of hydrogen gas were charged into the above-mentioned autoclave equipped with a stirrer containing the prepared polymerization catalyst, and preliminary polymerization was carried out at 20° C. for 5 minutes, followed by heating and carrying out the first-stage homopolypropylene (homoPP) polymerization reaction at 70° C. for 75 minutes. Thereafter, the pressure was returned to normal, and the inside of the reactor was replaced with nitrogen gas, after which the autoclave was weighed, and the polymerization activity of the homogeneous stage (first stage) was calculated by subtracting the tare weight of the autoclave and using the following calculation formula (i) for polymerization activity.
[0149] The polymerization activity (g-PP / (g-cat·hour)) shown in the following formula (i) represents the amount of polymer produced (g) per gram of solid catalyst component and per hour of polymerization time. Polymerization activity (g-PP / (g-cat · hour)) = (amount of polymer produced (g) / (solid catalyst component (g) · 1 hour))) (i)
[0150] Next, ethylene / propylene / hydrogen were charged into the reactor so that the molar ratio was 1.0 / 1.0 / 0.043, respectively, and then the temperature was raised to 70°C. While introducing ethylene / propylene / hydrogen so that the respective liters / minute ratio was 2.0 / 2.0 / 0.086, the reaction was carried out under conditions of 1.2 MPa, 70°C, and 1 hour to obtain an ethylene-propylene block copolymer.
[0151] The copolymerization (ICP) activity (g-ICP / (g-cat·hour)) during the formation of the resulting ethylene-propylene copolymer was calculated using the following formula (ii) for calculating ethylene-propylene block copolymerization activity. Copolymerization (ICP) activity (g-ICP / (g-cat·hour)) = ((I(g)-G(g)) / (mass of solid catalyst component contained in olefin polymerization catalyst (g)·1 hour)) (ii)
[0152] In the above formula (ii), I is the mass (g) of the autoclave after the copolymerization reaction is completed, and G is the mass (g) of the autoclave after the homopolymerization of PP is completed and the unreacted monomer is removed. The results are shown in Table 1.
[0153] <Increase in polymerization activity> The total polymerization activity was calculated as the sum of the polymerization activity in the homogeneous stage (first stage) and the copolymerization (ICP) activity during the formation of an ethylene-propylene copolymer, and this was designated as the total polymerization activity A.
[0154] Next, the total polymerization activity when the polymerization catalyst was formed in a nitrogen atmosphere (corresponding to Comparative Example 1 described later) was similarly determined as the total polymerization activity B, and the polymerization activity increase rate (%) was calculated according to the following formula (iii). The results are shown in Table 1. Polymerization activity increase rate (%) = (total polymerization activity A / total polymerization activity B) × 100 (iii)
[0155] In each of the following examples, the total polymerization activity A was also determined, and the total polymerization activity B of the corresponding comparative example in which the polymerization catalyst was formed in a nitrogen atmosphere was also determined, and the polymerization activity increase rate was calculated in the same manner as above.
[0156] <Xylene solubles in polymer (XS)> The proportion (XS) of p-xylene soluble matter in the resulting propylene homopolymer (homoPP) was determined by the following method. In a flask equipped with a stirrer, 4.0 g of the polymer (polypropylene) obtained from the first stage homopolypropylene polymerization and 200 mL of p-xylene were charged, and the temperature of p-xylene inside the flask was maintained below the boiling point (137 to 138 ° C) by setting the external temperature to above the boiling point of xylene (about 150 ° C), and the polymer was dissolved over 2 hours while maintaining the temperature of p-xylene inside the flask below the boiling point (137 to 138 ° C). The liquid temperature was then cooled to 23 ° C over 1 hour, and the insoluble and soluble components were filtered and separated. The solution of the above-mentioned soluble components was collected, and p-xylene was distilled off by heating and drying under reduced pressure, and the obtained residue was taken as the xylene soluble component (XS), and its mass was calculated as a relative value (mass%) to the polymer (polypropylene). The results are shown in Table 1.
[0157] Example 2 The atmosphere inside a 2.0-liter autoclave equipped with a stirrer (propylene concentration: 0.04 mol / L) was replaced with propylene gas (olefins), and 2.4 mmol of triethylaluminum (organoaluminum compound (B)) was charged into the autoclave (preliminarily contacted with 27 kmol of propylene gas per mole of titanium constituting the solid catalyst component (A1) described below), followed by maintaining the temperature at 20° C. for 1 minute.
[0158] Next, the solid catalyst component (A1) obtained in Production Example 1 was charged in an amount of 0.003 mmol in terms of titanium atom, and 0.24 mmol of cyclohexylmethyldimethoxysilane (CMDMS) (external electron donor compound (C)) was charged into the autoclave, and the internal temperature of the autoclave was maintained at 20° C. for 1 minute to prepare a polymerization catalyst.
[0159] Thereafter, an ethylene-propylene block copolymer was produced in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0160] Example 3 The atmosphere inside a 2.0-liter autoclave 1 equipped with a stirrer (propylene concentration: 0.04 mol / L) was replaced with propylene gas (olefins), and 0.003 millimole, calculated as titanium atom, of the solid catalyst component (A1) obtained in Production Example 1 was charged into the autoclave 1 (preliminarily contacted with 27 kilomoles of propylene gas per mole of titanium constituting the solid catalyst component (A1)), and the mixture was maintained at 20° C. for 1 minute.
[0161] The atmosphere inside a 2.0-liter autoclave 2 equipped with a stirrer (propylene concentration: 0.04 mol / L) was replaced with propylene gas (olefins), and 2.4 mmol of triethylaluminum (organoaluminum compound (B)) was charged into the autoclave 2 (preliminarily contacted with 27 kmol of propylene gas per mole of titanium constituting the solid catalyst component (A1)) and maintained at 20° C. for 1 minute.
[0162] Next, the entire content of the autoclave 2 and 0.24 mmol of cyclohexylmethyldimethoxysilane (CMDMS) (external electron donor compound (C)) were charged into the autoclave 1, and the internal temperature of the autoclave was maintained at 20° C. for 1 minute to prepare a polymerization catalyst.
[0163] Thereafter, an ethylene-propylene block copolymer was produced in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0164] Comparative Example 1 The atmosphere inside a 2.0-liter autoclave equipped with a stirrer was replaced with nitrogen gas (inert gas) (nitrogen gas concentration: 0.04 mol / L), and 0.003 mmol, calculated as titanium atom, of the solid catalyst component (A1) obtained in Production Example 1 was charged into the autoclave and maintained at 20° C. for 1 minute.
[0165] Next, 2.4 mmol of triethylaluminum (organoaluminum compound (B)) and 0.24 mmol of cyclohexylmethyldimethoxysilane (CMDMS) (external electron donor compound (C)) were charged into the autoclave, and the internal temperature of the autoclave was maintained at 20° C. for 1 minute to prepare a polymerization catalyst.
[0166] Thereafter, an ethylene-propylene block copolymer was produced in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0167] (Production Example 2) A solid catalyst component (A2) was prepared in the same manner as in Production Example 1, except that 6.9 mL (30.7 mmol) of diethyl benzylidenemalonate (BMDE) was added as the internal electron donor compound instead of diethyl 1-cyclohexene-1,2-dicarboxylate (CHDCDE) during heating up to 105° C. The titanium content in the obtained solid catalyst component (A2) was measured and found to be 2.2 mass%.
[0168] Example 4 A polymerization catalyst was prepared in the same manner as in Example 1, except that the solid catalyst component (A2) obtained in Production Example 2 was used, an ethylene-propylene block copolymer was produced, and the copolymer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0169] Comparative Example 2 Except for changing the gas for replacing the atmosphere inside the autoclave during the formation of the polymerization catalyst from propylene gas to nitrogen gas (nitrogen gas concentration during the polymerization reaction: 0.04 mol / L), the polymerization catalyst was formed in the same manner as in Example 4, an ethylene-propylene block copolymer was produced, and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0170] (Production Example 3) After thoroughly replacing the inside of a 500 mL round-bottom flask equipped with a stirrer with nitrogen gas, 20 g of diethoxymagnesium and 60 mL of toluene were placed in the round-bottom flask to obtain a diethoxymagnesium-containing liquid suspension.
[0171] Next, the inside of a 500 mL round-bottom flask equipped with a stirrer was thoroughly replaced with nitrogen gas, and 50 mL of toluene and 40 mL of titanium tetrachloride were added to the round-bottom flask to obtain a mixed solution of these. Next, the diethoxymagnesium-containing liquid was added to this toluene-titanium tetrachloride mixed solution to form a suspension.
[0172] The resulting suspension was then reacted at -6°C for 1 hour, after which 2.9 mL (18.1 mmol) of 2-ethoxyethyl-1-ethyl carbonate (EEECA) and 2.7 mL (10.8 mmol) of 2-isopropyl-2-isopentyl-1,3-dimethoxypropane (IIDMP) were added as internal electron donor compounds, and the resulting suspension was heated to 100°C and then reacted with stirring for 1.5 hours.
[0173] After the reaction was completed, the supernatant was removed from the suspension to obtain a precipitate, which was then washed four times with 150 mL of toluene at 90° C. to obtain a reaction product. 40 mL of titanium tetrachloride and 80 mL of toluene were added to the reaction product, and the mixture was heated to 100° C. and reacted for 15 minutes to obtain a reaction product. After repeating this process four times, the reaction product was washed six times with 150 mL of n-heptane at 40° C. and subjected to solid-liquid separation to obtain a solid catalyst component (solid catalyst component (A3)).
[0174] The titanium atom content in the obtained solid catalyst component (A3) was measured and found to be 2.3 mass %.
[0175] Example 5 A polymerization catalyst was prepared in the same manner as in Example 1, except that the solid catalyst component (A3) obtained in Production Example 3 was used and the internal temperature of the autoclave equipped with a stirrer during the preparation of the polymerization catalyst was changed from 20° C. to 10° C., and an ethylene-propylene block copolymer was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0176] Comparative Example 3 Except for changing the gas for replacing the atmosphere inside the autoclave during the formation of the polymerization catalyst from propylene gas to nitrogen gas (nitrogen gas concentration during the polymerization reaction: 0.04 mol / L), the polymerization catalyst was formed in the same manner as in Example 5, an ethylene-propylene block copolymer was produced, and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0177] (Production Example 4) A solid catalyst component (A4) was prepared in the same manner as in Example 5, except that the amount of EEECA added was changed from 2.6 mL to 2.9 mL and the amount of IIDMP added was changed from 2.9 mL to 2.6 mL. The titanium content in the obtained solid catalyst component (A4) was measured and found to be 2.7 mass%.
[0178] Example 6 A polymerization catalyst was prepared in the same manner as in Example 1, except that the solid catalyst component (A4) obtained in Production Example 4 was used, and an ethylene-propylene block copolymer was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0179] Comparative Example 4 Except for changing the gas for replacing the atmosphere inside the autoclave during the formation of the polymerization catalyst from propylene gas to nitrogen gas (nitrogen gas concentration during the polymerization reaction: 0.04 mol / L), the polymerization catalyst was formed in the same manner as in Example 6, an ethylene-propylene block copolymer was produced, and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0180] Example 7 Except for changing the internal temperature of the autoclave equipped with a stirrer during the formation of the polymerization catalyst from 20° C. to 40° C., the polymerization catalyst was prepared in the same manner as in Example 6, an ethylene-propylene block copolymer was produced, and the copolymer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0181] Comparative Example 5 Except for changing the gas for replacing the atmosphere inside the autoclave during the formation of the polymerization catalyst from propylene gas to nitrogen gas (nitrogen gas concentration during the polymerization reaction: 0.04 mol / L), the polymerization catalyst was formed in the same manner as in Example 7, an ethylene-propylene block copolymer was produced, and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0182] Example 8 Except for changing the gas for replacing the atmosphere inside the autoclave during the formation of the polymerization catalyst from propylene gas to ethylene gas (ethylene gas concentration during the polymerization reaction: 0.04 mol / L), the polymerization catalyst was formed in the same manner as in Example 6, an ethylene-propylene block copolymer was produced, and the copolymer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0183] (Production Example 5) As an internal electron donor compound, 10.2 mL (41.3 mmol) of dimethyl diisobutylmalonate (DIBMDM) was added instead of IIDMP, and the timing of adding EEECA was changed from after the suspension was reacted at -6°C for 1 hour to the fourth step of adding 40 mL of titanium tetrachloride and 80 mL of toluene to the resulting reaction product, heating to 100°C, and reacting for 15 minutes. Except for changing the amount of EEECA added from 2.9 mL to 0.24 mL, a solid catalyst component (A5) was prepared in the same manner as in Production Example 3. The titanium content in the resulting solid catalyst component (A5) was measured and found to be 2.3 mass%.
[0184] Example 9 A polymerization catalyst was prepared in the same manner as in Example 1, except that the solid catalyst component (A5) obtained in Production Example 5 was used, and an ethylene-propylene block copolymer was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0185] Comparative Example 6 Except for changing the gas for replacing the atmosphere inside the autoclave during the formation of the polymerization catalyst from propylene gas to nitrogen gas (nitrogen gas concentration during the polymerization reaction: 0.04 mol / L), the polymerization catalyst was formed in the same manner as in Example 9, an ethylene-propylene block copolymer was produced, and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0186] Example 10 Except for changing the gas for replacing the atmosphere inside the autoclave during the formation of the polymerization catalyst from propylene gas to ethylene gas (ethylene gas concentration during the polymerization reaction: 0.04 mol / L), the polymerization catalyst was formed in the same manner as in Example 9, an ethylene-propylene block copolymer was produced, and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0187] (Production Example 6) A solid catalyst component (A6) was prepared in the same manner as in Example 1, except that, as the internal electron donor compound, 7.2 mL (27.0 mmol) of dibutyl phthalate (DBP) was used instead of 6.4 mL (31.6 mmol) of diethyl 1-cyclohexene-1,2-dicarboxylate (CHDCDE), and the atmosphere during the formation of the polymerization catalyst was changed from a propylene gas atmosphere to a nitrogen gas atmosphere (nitrogen gas concentration: 0.04 mol / L).
[0188] The titanium atom content in the obtained solid catalyst component (A6) was measured and found to be 2.9 mass %.
[0189] (Reference example 1) A polymerization catalyst was prepared in the same manner as in Example 1 except that the solid catalyst component (A6) of Production Example 6 was used, and an ethylene-propylene block copolymer was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0190] In Table 1, the sum of the polymerization activity value during the homopolypropylene (homoPP) polymerization reaction and the copolymerization activity value during the ethylene-propylene block copolymerization reaction is shown as the total polymerization activity value.
[0191] [Table 1]
[0192] (Production Example 7) <Preparation of solid catalyst component> After thoroughly replacing the inside of a 500 mL round-bottom flask equipped with a stirrer with nitrogen gas, 20 g of diethoxymagnesium, 60 mL of toluene, and 0.45 mL (1.8 mmol) of 2-isopropyl-2-isopentyl-1,3-dimethoxypropane (IIDMP) were placed in the round-bottom flask to obtain a suspension containing diethoxymagnesium.
[0193] Next, the inside of a 500 mL round-bottom flask equipped with a stirrer was thoroughly replaced with nitrogen gas, and 50 mL of toluene and 40 mL of titanium tetrachloride were added to the round-bottom flask to obtain a mixed solution of these. Next, the diethoxymagnesium-containing liquid was added to this toluene-titanium tetrachloride mixed solution to form a suspension.
[0194] Next, the resulting suspension was reacted at -6°C for 30 minutes, and then heated to 10°C for 30 minutes. Then, 2.9 mL (18.1 mmol) of 2-ethoxyethyl-1-ethyl carbonate (EEECA) and 0.9 mL (3.6 mmol) of 2-isopropyl-2-isopentyl-1,3-dimethoxypropane (IIDMP) were added as internal electron donor compounds, and the resulting suspension was heated to 100°C and reacted with stirring for 1.5 hours.
[0195] After the reaction was completed, the supernatant was removed from the suspension to obtain a precipitate, which was then washed four times with 150 mL of toluene at 90° C. to obtain a reaction product. 20 mL of titanium tetrachloride and 100 mL of toluene were added to the reaction product, and the mixture was heated to 100° C. and reacted for 15 minutes to obtain a reaction product. After repeating this process four times, the reaction product was washed six times with 150 mL of n-heptane at 40° C. and subjected to solid-liquid separation to obtain a solid catalyst component (A7).
[0196] The titanium atom content in the obtained solid catalyst component (A7) was measured and found to be 2.1 mass %.
[0197] Example 11 <Formation of polymerization catalyst> The atmosphere inside a 2.0 L autoclave equipped with a stirrer was thoroughly replaced with nitrogen, and 0.9 mmol of triethylaluminum (organoaluminum compound (B)), 0.09 mmol of cyclohexylmethyldimethoxysilane (CMDMS) (external electron donor compound (C)), and 4.5 mmol of propylene as an additive were placed in the autoclave. Then, 0.0018 mmol of the solid catalyst component (A7) in terms of titanium atom was charged, and the internal temperature of the autoclave was maintained at 20° C. for 5 minutes to prepare a polymerization catalyst.
[0198] <Production of polypropylene> 12 moles of liquefied propylene and 67 mmol of hydrogen gas were charged into the above-mentioned autoclave equipped with a stirrer containing the prepared polymerization catalyst, and prepolymerization was carried out at 20°C for 5 minutes. The temperature was then raised, and polymerization reaction was carried out at 70°C for 60 minutes to obtain a propylene homopolymer.
[0199] The polymerization activity (g-PP / (g-cat·hour)) during the formation of the resulting propylene homopolymer was calculated using the following formula (iv). The results are shown in Table 2. Propylene homopolymerization activity (g-PP / (g-cat·hour)) = amount of PP obtained (g) / (mass of solid catalyst component contained in olefin polymerization catalyst (g)·1 hour)) (iv)
[0200] <Increase in polymerization activity> The polymerization activity was compared with that when the polymerization catalyst was formed under a nitrogen atmosphere without any additives (Comparative Example 7 described below), and the polymerization activity increase rate (%) was calculated according to the following formula (v). The results are shown in Table 2. Polymerization activity increase rate (%) = (polymerization activity (with additive) / polymerization activity (without additive)) × 100 (v)
[0201] Comparative Example 7 A polymerization catalyst was prepared in the same manner as in Example 11, except that no additive was charged in the autoclave during preparation of the polymerization catalyst, and a propylene homopolymer was produced and evaluated in the same manner as in Example 11. The results are shown in Table 2.
[0202] Example 12 A polymerization catalyst was prepared in the same manner as in Example 11, except that 1.8 mmol of 1-hexene was charged in the autoclave instead of propylene as an additive during the preparation of the polymerization catalyst, and a propylene homopolymer was produced and evaluated in the same manner as in Example 11. The results are shown in Table 2.
[0203] Example 13 A polymerization catalyst was prepared in the same manner as in Example 11, except that 0.90 mmol of 1,5-hexadiene was charged into the autoclave instead of propylene as an additive during the preparation of the polymerization catalyst, and a propylene homopolymer was produced and evaluated in the same manner as in Example 11. The results are shown in Table 2.
[0204] Example 14 A polymerization catalyst was prepared in the same manner as in Example 11, except that 1.8 mmol of 1,5-hexadiene was charged into the autoclave instead of propylene as an additive during the preparation of the polymerization catalyst, and a propylene homopolymer was produced and evaluated in the same manner as in Example 11. The results are shown in Table 2.
[0205] Example 15 Except for preparing the polymerization catalyst at 40° C. and charging 1.8 mmol of 4-methyl-1-pentene instead of propylene as an additive into the autoclave, the polymerization catalyst was prepared in the same manner as in Example 11, a propylene homopolymer was produced, and the evaluation was performed in the same manner as in Example 11. The results are shown in Table 2.
[0206] [Table 2]
[0207] The results in Tables 1 and 2 show that the olefin polymerization catalysts obtained in Examples 1 to 15 are those in which at least one selected from the solid catalyst component (A) and the specific organoaluminum compound (B) has been previously contact-treated with a hydrocarbon compound having one or more vinyl groups, and therefore exhibit excellent catalytic activity during the polymerization of olefins by suppressing a decrease in polymerization activity caused by early deactivation of active sites after catalyst formation, and are capable of producing olefin polymers with excellent stereoregularity.
[0208] In contrast, the results of Tables 1 and 2 show that, in the olefin polymerization catalysts obtained in Comparative Examples 1 to 7, neither the solid catalyst component (A) nor the specific organoaluminum compound (B) was previously contact-treated with a hydrocarbon compound having one or more vinyl groups, and therefore the deactivation of the catalytic active sites proceeded due to an excessive reaction with the organoaluminum compound, making it impossible to exhibit the desired catalytic activity, and the obtained polymers had high XS and poor stereoregularity. [Industrial Applicability]
[0209] According to the present invention, it is possible to provide a method for producing a catalyst for polymerization of olefins, which exhibits excellent catalytic activity during polymerization of olefins by suppressing a decrease in polymerization activity due to early deactivation of active sites after catalyst formation, and which is capable of producing an olefin polymer having excellent stereoregularity, a catalyst for polymerization of olefins, and a method for producing an olefin polymer.
Claims
1. A solid catalyst component (A) containing a compound having magnesium, titanium, a halogen and a carbonate group; The following general formula (I): R 1 p AlQ 3-p (I) (In the formula, R 1 is an alkyl group having 1 to 6 carbon atoms, Q is a hydrogen atom or a halogen atom, and p is a real number satisfying 0<p≦3. and an organoaluminum compound (B) represented by the formula: A method for producing a catalyst for olefin polymerization, characterized in that at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) is previously contacted with a hydrocarbon compound having one or more vinyl groups.
2. 2. The method for producing a catalyst for olefin polymerization according to claim 1, wherein the solid catalyst component (A) is previously contacted with a hydrocarbon compound having one or more vinyl groups.
3. 2. The method for producing a catalyst for olefin polymerization according to claim 1, wherein the organoaluminum compound (B) is previously contacted with a hydrocarbon compound having one or more vinyl groups.
4. the amount of at least one selected from the solid catalyst component (A) and the organoaluminum compound (B) to be pre-contacted with a hydrocarbon compound having one or more vinyl groups is The amount is 1 mole or more per mole of titanium constituting the solid catalyst component (A) used in the production of an olefin polymerization catalyst. The method for producing the catalyst for olefin polymerization according to claim 1 .
5. 2. The method for producing a catalyst for olefin polymerization according to claim 1, wherein the hydrocarbon compound having one or more vinyl groups is one or more selected from the group consisting of ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1,4-hexadiene, 1,5-hexadiene, 1,6-octadiene, 1,7-octadiene, 1-heptene, 1-octene, vinylcyclohexane and vinylcyclohexene.
Citation Information
Patent Citations
Ingredient and catalyst for olefin polymerization
JP1982063310A
Vapor phase preparation of propylene polymer of high bulk density
JP1993194637A
Catalyst for producing ethylene-propylene copolymer rubber
JP1995173213A
Production of olefin polymer
JP1998036430A
Production method for dialkoxy magnesium, and solid catalyst component and catalyst for polymerization of olefins
JP2004269467A